Intravenous lipid emulsion for the treatment of poisonings in 313 dogs and 100 cats (2016–2020) - Markert, Carina; Heilmann, Romy Monika; Kiwitz, Dschaniena; Doerfelt, René (Frontiers in Veterinary Science, 2023)
The aim of this retrospective study was to analyze the effect and potential adverse effects of intravenous lipid emulsion (ILE) in poisoned dogs and cats over a 5-year period.Methods: Medical records of 313 dogs and 100 cats receiving ILE between 2016-2020 were analyzed for suspected toxicant, clinical signs, ILE dosages and frequency, the effect and adverse effects of ILE, and patient outcome.Results: Dogs and cats were poisoned with mostly unidentified toxicants (48%), rodenticides (8%), recreational drugs and nuts (7% each) and other toxicants. Clinical signs included neurologic deficits (63%), cardiovascular signs (29%), thermoregulation (21%) or gastrointestinal abnormalities (17%). Treatment with ILE was initiated within a median of 6.0 hours (1.0-91.0 hours) after poisoning. Dogs and cats received a total amount of median 8.0 ml/kg (1.5-66.6 ml/kg) and 15.8 ml/kg (1.8-69.4 ml/kg) ILE, respectively. A positive effect was observed in 74% of the patients, whereas clinical signs worsened in 4% of the patients after ILE administration.No subjective effect was detected in 22% of the patients. Suspected or possible adverse effects of ILE occurred in 6% of the patients, including neurological signs (temporarily reduced consciousness and ataxia), bradycardia, hyperthermia, vomiting, diarrhea, respiratory distress, worsening of the general behaviour, facial swelling, and thrombophlebitis. The overall survival rate was 96%. One dog who potentially experienced adverse events was euthanized.ILE treatment was successful in most patients but can be associated with adverse effects. Administration of ILE should be carefully selected on an individual basis after weighing the possible benefits against potential adverse effects.